PENANAMAN NILAI-NILAI NASIONALISME MELALUI PERTUNJUKAN SENI DAN BUDAYA - Arum Wahyu Pramitasari (Institut Pendidikan Tapanuli Selatan, 2021)
Currently the forms of threats are increasingly varied and complex. If in the past the most dominant threat was the military threat, now non-military threats are something that should be considered, especially since Indonesia is a heterogeneous nation with various races, ethnicities, languages, religions, customs and different cultures in it. Based on astagatra, Indonesia's national security is divided into 2, namely Trigatra or 3 natural aspects (Population/Demography, Geography, Natural Resources,) and Pancagatra or 5 social aspects (Economy, Ideology, Defense and Security, Politics and Socio-Cultural). Currently, the potential form of threat faced by Indonesia is a threat with a socio-cultural dimension. To deal with this, innovation is needed to increase awareness of Nationalism and State Defense. As a preventive form of defense management, strengthening nationalism, the spirit of defending the country and the feeling of love for the homeland through cultural arts looks more friendly. For example, by inserting elements of nation and state in an art performance. In order to support the formation of defense policies in the socio-cultural field, the theory of community participation can be used. If every region in Indonesia has an annual event for arts and culture with high demand, it will be easier to implement the policy. Art and cultural events wrapped in the nuances of love for the homeland will indirectly foster nationalism and the spirit of defending the country to support national defense